The Effectiveness of Interactive Nutrition Education among Adolescents in Islamic Boarding Schools Toward a Healthy Lifestyle - Salsabila Romadona; Muhammad Sabilul Firdaus; Venna Arzika Humaida (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Adolescents in Islamic boarding schools often experience limited access to health information and nutrition education, which can lead to unhealthy dietary behaviors and low awareness of balanced nutrition. Improving health literacy at this stage is essential to promote lifelong healthy habits. However, evidence regarding the effectiveness of interactive nutrition education in this specific educational context remains limited. This study aimed to evaluate the effectiveness of interactive nutrition education in improving the knowledge and attitudes of adolescents in an Islamic boarding school toward a healthy lifestyle. A quasi-experimental design with a one group pretest posttest approach was conducted among 30 students. The intervention consisted of interactive nutrition education sessions combining discussion, games, and visual media. Data on knowledge and attitudes were collected using validated and reliable instruments (Cronbach’s Alpha = 0.708 for cognitive and 0.848 for attitude). Statistical analyses included paired t-tests and Wilcoxon Signed Rank Tests to assess differences before and after the intervention. The results showed a significant improvement in students’ knowledge after the intervention (t(29) = 7.581, p < 0.001), indicating that interactive nutrition education effectively enhanced cognitive understanding of healthy nutrition. Meanwhile, although the average attitude score increased after the intervention, the difference was not statistically significant (p = 0.131). These findings suggest that while knowledge improved significantly, behavioral and attitudinal changes may require longer or repeated exposure to reinforcement activities. Interactive nutrition education is effective in improving adolescents’ nutritional knowledge in Islamic boarding schools and serves as a promising strategy for promoting healthy lifestyles. Future programs should incorporate continuous reinforcement and experiential learning to sustain attitudinal and behavioral change.